Debt-to-Income Ratio and Financial Vulnerability of Rural Households: Evidence from Weekly Microfinance Practices in Boawae District, Nagekeo Regency - Maria Yasinta Deme; Ernesta Wae (Journal of Business, Accounting and Information Technology, 2026)
The proliferation of weekly microfinance known as "koperasi mingguan" in rural areas provides quick credit access but introduces severe financial risks for rural households. This study aims to analyze the Debt-to-Income (DTI) ratio, determine financial vulnerability levels, and identify the key factors driving financial distress across 7 villages in Boawae District, Nagekeo Regency. Using a quantitative descriptive and inferential approach, data from 149 rural households were analyzed using descriptive statistics and Ordinary Least Squares (OLS) regression via SPSS. The empirical results reveal a critical situation: the average DTI ratio across the sub-district reaches 89.35%, and 68.46% of surveyed households suffer from structural financial deficits. Spatially, Rowa, Raja Selatan, and Gerodhere villages face severe debt traps with average DTI ratios exceeding 100%. Furthermore, regression analysis confirms that the number of weekly cooperatives joined is the single most significant factor undermining household financial health (β = 41.436, p = 0.000), meaning every additional cooperative membership spikes the DTI ratio by 41.44%. Occupationally, casual laborers and weavers suffer from the highest financial vulnerability. This study implies that local governments must implement stricter regulations on informal micro-lending and initiate gender-responsive financial education in rural Nagekeo.